Effects of low‐intensity, elastic band resistance exercise combined with blood flow restriction on muscle activation. Issue 1 (27th June 2012) - Yasuda, T.; Fukumura, K.; Fukuda, T.; Iida, H.; Imuta, H.; Sato, Y.; Yamasoba, T.; Nakajima, T.
<x xml:space="preserve">Abstract</x> We examined the effects of blood flow‐restricted, low‐intensity resistance exercise (termed kaatsu) using an elastic band for resistance on muscle activation. Nine men performed triceps extension and biceps flexion exercises (four sets respectively) using an elastic band for resistance with blood flow restriction (BFR) or CON (unrestricted blood flow). During a BFR session, subjects wore pressure cuffs inflated to 170–260 mmHg on the proximal region of both arms. Surface electromyography (EMG) was recorded from the triceps brachii and biceps brachii muscles, and mean integrated EMG (iEMG) was analyzed. Blood lactate concentration was obtained before (Pre) and immediately after two exercises (Post). During triceps extension and biceps flexion exercises, muscle activation increased progressively (P < 0.05) under BFR (46% and 69%, respectively) but not under CON (12% and 23%, respectively). Blood lactate concentration at Post was higher (P < 0.05) under BFR than under CON (3.6 and 2.1 mmol/L, respectively). Blood lactate concentration at Post was significantly correlated with increased iEMG in both triceps extension (r = 0.65, P < 0.01) and biceps flexion exercises (r = 0.52, P < 0.05). We conclude that kaatsu training using elastic bands for resistance enhances muscle activation and may be an effective method to promote muscle hypertrophy in older adults or patients with a low level of activity.